MANAJEMEN KEUANGAN UNTUK PERTUMBUHAN PERUSAHAAN - Ciptawan (MTU PRESS, 2024)
This paper discusses the impact of financial management on the success of Small and Medium Enterprises (SMEs). Beginning with the definition of SMEs, it emphasizes that effective financial management is crucial for business sustainability. SME owners need to understand financial concepts, make informed decisions, and prioritize financial planning to ensure their business operates optimally.Real-world case studies illustrate how successful SMEs implement sound financial management strategies. Additionally, this research explores government policies and support in SME financial management, including assistance programs, tax incentives, and access to financial advisory services. Government interventions play a vital role in providing resources and guidelines that help SMEs manage their finances effectively.This paper also examines future developments that may influence SME financial management, such as advancements in technology (AI, blockchain, IoT) and regulatory changes. Furthermore, it discusses challenges in financial forecasting and the growing pressure to leverage data analytics and predictive modeling to enhance the accuracy of financial decision-making.